Serous endometrial carcinoma with cardiac metastasis (a case report) - M. V. Zavyalova; S. V. Vtorushin; N. S. Telegina; I. G. Kutsenko; I. V. Dolgalev; M. A. Egunova (ABV-press, 2023)
Cardiac metastasis from endometrial cancer is a very rare finding. The article presents a case of death, demonstrating the aggressive clinical course of endometrial serous carcinoma. In this clinical example the disease was accompanied by generalized metastasizing through a lymphogenous route to unexpected distant organs (peribronchial lymph nodes, pleura, pericardium).